Artikel Review: Kandungan Senyawa Aktif Tanaman Untuk Kesehatan Kulit - Gunarti, Neni; Yuniarsih, Nia; Toni. S, Rifqi Maulana; Khoerunnisa, Rita; Allahuddin, Allahuddin; Anggraeni, Fera; Ruhdiana, Tita (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2022)
Abstract: Background: Skin is the outermost organ of the body that coats the human body that needs to be treated to prevent skin damage from free radicals or infection. The way to maintain and care for the skin is using synthetic compounds that can help maintain healthy skin. Another alternative in skin care is to use plants that have active compounds that are beneficial for skin health and have relatively low side effects compared to synthetic chemicals. Objective: This study aimed to determine the active compounds of plants that can improve skin health. Method: Article review using Google Schoolar database with keywords related to the research topic, namely "Active Compounds, Plants, Health, Skin". Journals used in the last 10 years (2012-2022). Results: The results of a literature review show that there are 10 plants that can improve skin health, namely yam (Pachyrhizus erosus), liquorice (Glycyrrhiza glabra), arceola cherry (Malpighia emarginata), aloe vera (Aloe vera), guava (Psidium guajava L.), tomato (Solanum lycopersicum L.), Moringa leaf (Moringa oleifera), papaya (Carica papaya L), avocado (Persea americana M.) and sweet orange (Citrus x aurantium L) The active compounds in these plants that are beneficial for skin health are alkaloids, terpenoids, phenolics, flavonoids, carotenoids, polyphenols, tannins, steroids, triterpenoids, vitamin-C, vitamin-B, niacinamide, lycopene, glabridin, saponins and antraquinones. Conclusion: Active plant compounds that are beneficial for skin health are alkaloids, terpenoids, phenolics, flavonoids, carotenoids, polyphenols, tannins, steroids, triterpenoids, vitamin-C, vitamin-B, niacinamide, lycopene,  glabridin, saponins and antraquinones.